Evolution of metropolitan airports in Japan: Air development in Tokyo and Osaka - Katsuhiro Yamaguchi (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
If one is asked to give an appraisal of airport development in metropolitan areas in Japan, an unsparing critic may not esteem it highly for three reasons. One, because planning for the secondary airport at Tokyo and Osaka was initiated too late to match growth in demand. Two, due to untimely planning, the original airport was exasperated with the noise issue by the time the search for the location of the secondary airport had begun. As a consequence, the location of the secondary airport had to be situated far from the city centre. Three, because improvements to access transport, to overcome the airport's distant location, were not planned thoroughly enough and have taken too much time to be completed, both the out-of-pocket costs and access time are still unsatisfactory.
Keywords: 330